Les usages de la mémoire : rhétorique du témoignage, espaces de mémoire et rapports de genres dans les dictatures du Brésil et du Paraguay - Janine Gomes da Silva (Centre de Recherches sur les Mondes Américains, 2014)
The memories of men and women present interesting aspects for reflecting on the dictatorship period and, in this paper, we intend to introduce some aspects of the “gendered” uses of memory in the Dictatorships of Brazil (1964-1985) and Paraguay (1954-1989), by means of a compared history. Our intention here is to observe how the various feminist groups were formed, how they operated, their relations with the military dictatorships and the resistance movements, and their processes for establishing identification and difference, among other themes. In the documentation on the dictatorships of these two countries, it is possible to observe how the marks of gender, apart from appearing in the narratives of different interviewees, were also used in discourses related to the resistance movements. This documentation awakens an interest in questioning how these sources (mainly, the documentation housed in Archives and Museums, and interviews carried out through the methodology of oral history) may, in different manners, contribute to a reflection in the field of memory and in gender studies.